A Theoretical Approximation of the Accelerating Effects of Ultrasound about the Extraction of Phenolic Compounds from Wood by Wine Spirits - Manuel J. Delgado-González; María de Valme García-Moreno; Dominico A. Guillén-Sánchez (Foods, 2022)
The acceleration on the extraction by the sonication of phenolic compounds (measured as the Total Phenolic Index) from wood chips by wine distillates is studied in the present paper. Using the Arrhenius equation, the theoretical temperature at which the kinetics obtained by these sonicated extraction processes are equal to the kinetics of non-sonicated and thermally accelerated extractions, was calculated. By applying a pseudo-second order kinetic model, it was shown that the initial rate values obtained from the sonicated extractions were as high as those obtained from the thermal extractions carried out at a temperature at least 2.5 °C higher than the real temperature at which the experiment was performed. Higher power densities lead to higher initial rates of extraction, although very high power densities decrease the amount of phenols in equilibrium, probably due to the degradation processes. Additionally, the positive synergy between the sonication and the movement of the recirculated distillate through wood chips was also stablished, obtaining a difference of temperature of at least,18.2 °C for the initial extraction rate and 7.0 °C for the equilibrium.